2020
DOI: 10.1111/jfpp.14931
|View full text |Cite
|
Sign up to set email alerts
|

Optimized preparation process for naringenin and evaluation of its antioxidant and α‐glucosidase inhibitory activities

Abstract: Diabetes mellitus (DM) is a common and frequently occurring disease that seriously endangers human health. As lifestyles have changed, DM has gradually developed into one of the most significant chronic diseases for mankind (Zhou, Lu, Liu, Pan, & Zhou, 2014). It is currently estimated that the number of diabetic patients in the world will increase from 240 to 642 million by 2040 (Reusch & Manson, 2017). In China, more than 100 million people will be suffering from tape 2 DM by the 2040s (Carracher, Marathe, & … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Here, we confirmed that naringenin has a higher affinity (ΔG = −7.2 kcal/mol) for interacting with α-glucosidase in its active site ( Figure S3 ). This result is consistent with prior research that suggested naringenin may have antidiabetic properties [ 45 , 46 , 47 ]. Naringenin, alongside naringin, both of which are abundant in the peel of Citrus species, shows high antidiabetic activity in type 2 diabetic rats induced by NA/STZ [ 17 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Here, we confirmed that naringenin has a higher affinity (ΔG = −7.2 kcal/mol) for interacting with α-glucosidase in its active site ( Figure S3 ). This result is consistent with prior research that suggested naringenin may have antidiabetic properties [ 45 , 46 , 47 ]. Naringenin, alongside naringin, both of which are abundant in the peel of Citrus species, shows high antidiabetic activity in type 2 diabetic rats induced by NA/STZ [ 17 ].…”
Section: Resultssupporting
confidence: 93%
“…Here, we confirmed that naringenin has a higher affinity (ΔG = −7.2 kcal/mol) for interacting with α-glucosidase in its active site (Figure S3). This result is consistent with prior research that suggested naringenin may have antidiabetic properties [45][46][47]. Naringenin, alongside naringin, both of which are abundant in the peel of The potential antidiabetic efficacy of different extracts from the peel of C. aurantium was revealed in this study by examining their inhibitory effects on α-amylase and αglucosidase in vitro.…”
Section: Inhibitory Activities Of Citrus Aurantium Peel Extracts Against Intestinal α-Glucosidase and Pancreatic α-Amylasesupporting
confidence: 91%
“…These results indicated that naringenin possessed neuroprotective and hypertensive inhibitory effects even though the in vitro enzyme inhibitory investigation suggested that naringenin was not a good inhibitor. Naringenin was also an effective inhibitor against α-glucosidase (IC 50 of 0.79 mM) comparing to acarbose, an anti-diabetic drug (IC 50 of 2.03 mM) [ 20 ]. Naringenin (25 mg/kg) could lower postprandial serum glucose levels in streptozotocin (STZ)-induced diabetic rats [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, naringin (18) was recorded to exhibit strong inhibition against both enzymes in the majority of studies involved. 61,86,[94][95][96][97] However, in two studies reported by Kong et al 95 and Zhang et al, 86 this compound was reported to inhibit α-glucosidase not as well as acarbose in the same condition, as the IC50 values stood at 27.2 mM and 22.1 mM, respectively. Therefore, further evidence is needed to confirm the potency of this compound.…”
Section: Flavanols (Catechins)mentioning
confidence: 93%
“…Naringenin (9) is the most well-studied flavanone with 16 studies employing this compound in their inhibition assay. 39,46,61,69,[77][78][79][80][81][82][83][84][85][86][87] Concerning the α-glucosidase inhibition, naringenin was recorded to exhibit stronger inhibitory activity than acarbose in the same condition in the majority of the reported results.…”
Section: Flavanols (Catechins)mentioning
confidence: 99%